Uneven Evolutions: Review of Mackenzie Cooley, The Perfection of Nature: Animals, Breeding, and Race in the Renaissance - Guest, Kristen (Humanimalia, 2023)
Mackenzie Cooley. The Perfection of Nature: Animals, Breeding, and Race in the Renaissance. Chicago: University of Chicago Press, 2022. xvi + 353 pp., 30 halftones. 37.50 (pb), 112.50 (hb), 36.99 (pdf).